Merge or fail? The determinants of mergers and bankruptcies in Switzerland, 1995-2000 - Stefan Buehler; Christian Kaiser; Franz Jaeger (University of Zurich, Socioeconomic Institute, 2005)
This paper examines the determinants of mergers and bankruptcies, using firm level data from the Swiss Business Census and the Dun & Bradstreet exit database for Switzerland (1995-2000). Employing duration analysis, we find considerable differences in the determinants of mergers and bankruptcies, in particular with respect to firm size, location and the impact of macroeconomic conditions. Our results support the notion that mergers are often undertaken to seize growth opportunities.
Keywords: C41; L10; L20; 330; merger; bankruptcy; failure; survival; exit; Fusion; Übernahme; Insolvenz; Unternehmenserfolg; Erfolgsfaktor; Schätzung; Schweiz; Statistische Bestandsanalyse